The Nature of Lightning in the Qur'an (Analytical Study of Fakhruddin Al-Razi's Interpretation in the Book of Mafatih Al-Ghoyb) - Mohammad Fattah; Arini Jamilatun Niswah (Penerbit Hellow Pustaka, 2025)
There are many verses in the Qur'an that explain the occurrence of thunder and lightning phenomena/events, all of these events are proof of the power and greatness of Allah SWT. Lightning has a very important role in the lives of all creatures on earth. However, there are times when it can cause disaster/danger for His creatures. Thunder and lightning are natural phenomena that occur when rain falls. Therefore, the nature of lightning will be the object of this research based on the interpretation of Mafa>tih al-Ghoyb by Fakhruddi>n Al-Ra>zi>. The problem that will be discussed in this research is the nature of lightning according to Fakhruddin Al-Ra>zi in the interpretation of Mafa>tih al-Ghoyb and will be explained in two focuses, namely: 1. What is the essence of lightning according to Fakhruddi>n Al-Ra>zi> in his book Mafa>tih al-Ghoyb)? 2. What are the benefits and dangers of lightning in identifying, collecting, processing and research related to lightning, whether in the form of the Koran according to Fakhruddi>n Al-Ra>zi> in his book Mafa>tih al-Ghoyb)? In this research, the author uses a library research approach, so steps will be taken on primary data and secondary data accurately and factually. Based on the results of this research, the greatness of Allah SWT will be revealed in His creation, especially regarding lightning, which in the Al-Qur'an is expressed in three words, namely Al-Ra'd, Al-Barq, and Al-Sa>'iqah. According to Fakhruddi>n Al-Ra>zi> interprets the meaning of the word Al-Ra'd as the sound heard from clouds colliding with each other caused by gusts of wind which cause them to collide with each other, Al-Barq is light coming out of the clouds accompanied by a strike. which strikes something so that it shines on it, and Al-Sa>'iqah is an explosion accompanied by a lightning strike accompanied by soft fire which can destroy something strongly, the speed of the strike cannot be matched and it immediately reaches the earth. Lightning is a direct guidance from Allah SWT to humans so that they always have devotion to Him and have a big role for His creatures. Lightning is good news for farmers because there will be a sign of rain that will fertilize the plants, a warning for humans to always glorify Allah SWT, wisdom for people who always remember the greatness of Allah SWT and a lesson for people who are wise.